HEAD TEACHERS’ INSTRUCTIONAL LEADERSHIP AND EFFECTIVENESS OF SECONDARY SCHOOLS IN BANGLADESH - Uddin, Mohammed Rashel; Akhter, Salma; Hena, Sharmin (Unnes Science Education Journal, 2018)
This paper is based on the study of Principals’ Instructional Leadership and School Effectiveness in Bangladesh. The main aim of this study was to examine the relationship between principals’ instructional leadership and effectiveness of the secondary schools of Bangladesh. It was carried out on the quantitative mode of research. As this study involves inquiring numerical data, a quantitative method was followed throughout the study. The major findings of the study showed that principals’ instructional leadership had positive impacts on students’ achievement, worthy classroom environment, respectable teaching-learning activities and above all maintaining decent academic standard of the school. The most important matter is that in Bangladesh there are some peripheral variables which impact the total education system such as political interruption, lack of awareness of community people, inadequate manpower in decision making level etc. As an instructional leader a principal with his/her strong instructional leadership skills can make the school environment impeccable and maintain a good affiliation with stakeholders. In this study, the researchers have found that the total effectiveness of a school mainly hinges on instruction and the schools which have a tendency to develop their systems must have a strong instructional leader. Instructional leadership doesn’t need an active environment but it can construct the environment effectively.